PREVALENCE OF DIAGNOSED AND UNDIAGNOSED DIABETES IN A RURAL COMMUNITY: A HOME-BASED SCREENING - Kandasamy, Krishnaveni; Rajagopal, Shanmuga Sundaram; Ramalingam, Kameswaran; Krishnan, Karthickeyan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Diabetes is one of the main global risks of mortality and is seen with a drastic rise in developing nations in accordance with rise in age. The main aim of the study is to find the prevalence of diabetes and pre-diabetes and its associated risk factors among the rural community based on diagnostic criteria. Methods: This cross-sectional study was conducted in a rural community of Salem district, Tamil Nadu, India. Patient data (demographics, lifestyle factors, and medical reports) were collected with the help of a questionnaire. Results: Of 780 populations, 425 were included for the screening of diabetes based on inclusion criteria. Of the 425 screened samples, 224 (52.7%) were diagnosed with diabetes. From these 224 diabetic cases, 133 (31.3%) were known cases of diabetes, 26 (6.1%) were newly diagnosed diabetic cases, and 65 (15.3%) were pre-diabetic cases. Most of the diabetic patients 140 (62.5%) were illiterate, and 159 (71%) were never had physical activities. A positive association (p<0.05) was observed between diabetes and age, body mass index (BMI) and tobacco use other than smoking. 65 patients were found to be pre-diabetes, among which 41.5% (27 cases) were male and 58.5% (38 cases) were female. A positive association (p<0.05) was observed between pre-diabetes and age, family history of diabetes and HTN, BMI, and lifestyle factors such as tobacco use, alcohol consumption, and smoking. Conclusion: Our study demonstrated that the burden of diabetes was observed to be increasing in India and it is becoming common among communities. Patient awareness and timely diagnosis and intervention may limit the progression of the disease.